Spectral Optimization to Minimize Light Absorbed by Artwork. Issue 1 (2nd January 2020) - Durmus, Dorukalp; Abdalla, Dianna; Duis, Aaron; Davis, Wendy
ABSTRACT: Light is needed to appreciate artwork, but visible radiation causes damage by photochemical action. Photons trigger photochemical action only when they are absorbed by the object. Damage to sensitive materials can be reduced by optimizing the spectrum of a light source to the reflectance factor of a museum artifact. Absorption minimization approaches can be utilized to quantify and optimize typically conflicting parameters, such as damage due to light absorption, color quality of artwork, and energy consumption. In this project, seven narrowband light emitting diodes (LEDs) are optimized using a multi-objective genetic algorithm to reduce light absorption and energy consumption, while maintaining the color appearance of five paints (blue, green, yellow, orange, red). Results indicate that optimized test spectra can reduce light absorption between 18% and 48%, without causing perceptible color or hue shifts in the paintings. Parallel to absorption, energy consumption is almost halved for all of the paints (between 42% and 48%). Optimizing the light source spectrum can aid in conservation of art collections in museums by reducing damage caused by optical radiation while preserving color fidelity.